EDAPHIC FAUNA IN SUSCEPTIBLE SOIL TO ARENIZATION IN THE SOUTHWEST OF RIO GRANDE DO SUL - Rovedder, Ana Paula (2004)
The edaphic fauna is used as an indicator of soil quality, due to its sensibility to environmental alterations. The objective of this study was to verify the effects of different uses of the soil on edaphic fauna in a sandy soil of the Southwest of Rio Grande do Sul. Four areas were selected: degraded area, no-tillage, native grassland and eucalyptus plantation. The organisms were collected with Provid traps, in October, November and December of 2001. For each soil use fauna abundance and diversity were determined considering the Ordem with greater occurrence. The Shannon index was also calculated. The Collembola group was studied until family level, due to its importance as biological indicator, having its abundance determined for each soil use. The higher abundance of edaphic fauna was found in eucalyptus, while the higher diversity was found in no-tillage. The degraded area presented the smallest abundance and diversity indexes. The levels of abundance and diversity found in eucalyptus were similar to those found in no-tillage and in native grassland. The degraded area presented the lowest indices of abundance and diversity of edaphic fauna and smallest abundance of Collembola, evidencing the characteristics of degradation of the environment.